A Review on Puncturing Potential: Microneedles' Present Landscape And Prospective Horizons - Rizwan, Boyeekati Mohammad; Mahammed, Nawaz; Taj, Shaik Farheen; Kumar, V. Sivasai Bharath; Yamuna, B. (Jordan Journal of Pharmaceutical Sciences, 2025)
Microneedle technology has emerged as a promising approach for drug delivery, vaccination, diagnostics, and cosmetic treatments. This review provides an overview of microneedle technology, covering the various types of microneedles, fabrication techniques, applications, advantages, challenges, safety considerations, clinical translation, and future perspectives. Solid, hollow, dissolving, coated, and hydrogel-forming microneedles are discussed, along with their structures, materials, and fabrication methods. Applications in drug delivery, vaccination, diagnostics, and cosmetic treatments are explored, with an emphasis on emerging and novel uses. The review highlights the advantages of microneedle technology, including enhanced patient compliance, improved drug absorption, and reduced pain, as well as challenges such as manufacturing scalability and regulatory approval. Fabrication techniques, biocompatibility, safety issues, clinical translation, and commercialization aspects are examined, along with future directions and emerging trends such as multifunctional microneedles and personalized medicine. Overall, microneedle technology holds tremendous promise for revolutionizing healthcare and biomedical engineering, but further research and development are required to address current challenges and realize its full potential.